# Problem Of The Week #433 September 8th, 2020

Status
Not open for further replies.

#### anemone

##### MHB POTW Director
Staff member
Here is this week's POTW:

-----

Show that if $a+b+c=0$, then $\left(\dfrac{a}{b-c}+\dfrac{b}{c-a}+\dfrac{c}{a-b}\right)\left(\dfrac{b-c}{a}+\dfrac{c-a}{b}+\dfrac{a-b}{c}\right)=9$.

-----

#### anemone

##### MHB POTW Director
Staff member
Congratulations to kaliprasad for his correct solution!

You can find the suggested solution as below:

Let $x=b-c,\,y=c-a,\,z=a-b$. Since $a+b+c=0$, we have

$y-z=b+c-2a=-3a$, by the same token we get $z-x=-3b$ and $x-y=-3c$.

By using the identity $\dfrac{y-z}{x}+\dfrac{z-x}{y}+\dfrac{x-y}{z}=-\dfrac{(y-z)(z-x)(x-y)}{xyz}$ for $x,\,y,\,z \ne 0$, and replacing the variables $x,\,y$ and $z$ with $a,\,b$ and $c$, we get

$\dfrac{-3a}{b-c}+\dfrac{-3b}{c-a}+\dfrac{-3c}{a-b}=-\dfrac{(-3a)(-3b)(-3c)}{(b-c)(c-a)(a-b)}$, which simplifies to

$\dfrac{a}{b-c}+\dfrac{b}{c-a}+\dfrac{c}{a-b}=-\dfrac{9abc}{(b-c)(c-a)(a-b)}$--(1)

Now, if we set $x=a,\,y=b$ and $z=c$ in the above identity, we get

$\dfrac{b-c}{a}+\dfrac{c-a}{b}+\dfrac{a-b}{c}=-\dfrac{(b-c)(c-a)(a-b)}{abc}$--(2)

Multiplying the last two equalities (1) and (2), we get the desired result.

Status
Not open for further replies.